Development and evaluation of bio-nanoparticles as novel drug carriers for the delivery of Selegiline (International Current Pharmaceutical Journal, 2016)
The purpose of the present study was to formulate and evaluate Selegiline loaded bio-nanoparticles for effective treatment of Depression. For the preparation of bio-nanoparticles biomaterial was isolated from fruits of Luffa acutangula by an economic method. The biomaterial recovered from the concentrate was subjected for various physicochemical properties like color, solubility, color changing point and chemical test. Bio-nanoparticles were prepared by modified solvent evaporation method in different batches with variable drug/biomaterial ratio. Prepared batches were subjected for various evaluation studies like particle size, zeta potential, SEM, TEM, surface entrapment, in-vitro diffusion, DSC and stability. Particle size and zeta potential result revealed that all nanoformulation were within range of 110 to 152.7 with slight negative in charge. SEM and TEM study report indicate that formulations were spherical in shape with less or no aggregation. Less surface entrapment leads to better drug entrapped inside nanomatrix. Bio-nanoformulations were capable of releasing the drug in a slow sustained manner. From the present investigation, it may be concluded that biomaterial isolated from fruits of Luffa acutangula used in the preparation of bio-nanoparticle act as an efficient carriers for deliver selegiline at a controlled rate. It may significantly improve the ability to cross blood-brain barrier and serve as an effective tool to treat Depression disease.Goswami et al., International Current Pharmaceutical Journal, March 2016, 5(4): 33-37http://www.icpjonline.com/documents/Vol5Issue4/01.pdf